Characterization and Expression Analysis of B12D-Like Gene From Pearl Millet. (December 2022) - Almutairi, Zainab M
B12D-Like is a member of the B12D domain-containing protein family, which includes several transmembrane proteins in plants. In this study, the cDNA of PgB12D-Like from Pennisetum glaucum subsp. monodii (Maire) Brunken was sequenced and characterized. The 446-bp cDNA for PgB12D-Like encodes for a deduced protein of 95 amino acids. The PgB12D-Like protein contains a B12D domain and a transmembrane helix embedded in the mitochondrial membrane. Cis-regulatory elements analysis reveals binding sites for various transcription factors involved in responses to stress, light, and plant hormones in the putative promoter sequence for PgB12D-Like . Several proteins involved in floral organ development were also found to have binding sites in the PgB12D-Like promoter, such as agamous-like proteins and squamosa promoter binding proteins. Real-time PCR reveals high expression of PgB12D-Like in flowers during heading, whereas its expression in a 4-day-old seedling shoot was the lowest. Moreover, cold, drought, and heat stress were found to upregulate PgB12D-Like, whereas gibberellic acid downregulated its expression in seedlings. The present study helps to uncover the function of the B12D-Like in response to plant hormones and abiotic stress during P. glaucum development.